Social computing and social media : design, ethics, user behavior, and social network analysis : 12th International Conference, SCSM 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings.: design, ethics, user behavior, and social network analysis : 12th International Conference, SCSM 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings. Part I (2020) - Unknown
No abstract available